Pembinaan Perilaku Hidup Bersih Dan Sehat Guna Mencegah Penyebaran Covid- 19 Di Tpq Darussalam Dusun Sukorejo Desa Kepung Kecamatan Kepung Kabupaten Kediri - Nikmatur Rodiah; M. Hanif Satria Budi (LP3M IAIFA Kediri, 2021)
Clean and healthy living (PHBS) is all health behaviors carried out above awareness, so that the family or closest people can help themselves or others in the field of health and play an active role in health activities in the community. Clean and healthy living behavior is basically an attempt to transmit an experience of clean and healthy living behavior through individuals, groups, or communities. By applying clean and healthy living behaviors will make yourself, out and society away from all diseases. Healthy and clean living behaviors can be applied in the environment of homes, workplaces, public places, and in health facilities (hospitals) especially in the school environment because it is a school where it is a place to print future generations. The goal of PHBS is to improve the quality of health through the process of counseling, mentoring, and coaching. While the main manfaaat of PHBS in school is to create a santri who are health conscious and have knowledge about living clean and healthy living behaviors that meet health standards. For this reason, the program of improving clean and healthy living behavior is needed among students, especially in non-formal schools such as (TPQ) with health conditions that are currently very concerned with the Covid-19 outbreak, which requires learners or students to always apply health protocols that have been set by the government